L’expérience de collaboration d’enseignantes des minorités visibles dans la (trans)formation d’étudiant[e]s d’origine immigrante inscrit[e]s dans un programme francophone de formation initiale en enseignement en Alberta - Jacquet, Marianne (Canadian Journal of Education/Revue canadienne de l'éducation, 2024)
This article focuses on the collaborative experience of a teacher in training and two visible minority teachers involved in the development and teaching of a new course designed to better prepare mature immigrant and visible minority students in Alberta francophone and French immersion school settings. Qualitative data were collected from the teachers using an interview and a survey to document this collaborative experience. Teachers agreed to participate in this project because of the proposed conceptual framework, which focused on the intercultural approach, reflective practice, and a perspective of equity and inclusion, as well as their own professional and personal commitment to the success and empowerment of pre-service students of immigrant origin. This commitment relies on two contrasting identity postures: of decolonization and of identification to a plural Albertan francophonie. In addition, the diversity of experiences and the common desire to work together promoted a high level of interdependence between team members, whose open-mindedness and flexibility contributed to making the collaboration a professional experience that was rich for the team and a source of empowerment for the two teachers.